2019
DOI: 10.33549/physiolres.933961
|View full text |Cite
|
Sign up to set email alerts
|

Various AKIP1 Expression Levels Affect Its Subcellular Localization but Have no Effect on NF-κB Activation

Abstract: A-kinase interacting protein 1 (AKIP1) has been shown to interact with a broad range of proteins involved in various cellular processes, including apoptosis, tumorigenesis, and oxidative stress suggesting it might have multiple cellular functions. In this study, we used an epitope-tagged AKIP1 and by combination of immunochemical approaches, microscopic methods and reporter assays we studied its properties. Here, we show that various levels of AKIP1 overexpression in HEK-293 cells affected not only its subcell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…A kinase-interacting protein 1, localizing in cytoplasm, nucleus, and mitochondria, functions as an adaptor of structural intracellular protein. 16 Recently, AKIP1 has been shown to facilitate tumorigenesis and invasiveness. [9][10][11][12] For example, one study displays that AKIP1 promotes cell migration, invasion, and EMT through mediating transactivating Zinc Finger E-Box Binding Homeobox 1 (ZEB1) in non-small-cell lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…A kinase-interacting protein 1, localizing in cytoplasm, nucleus, and mitochondria, functions as an adaptor of structural intracellular protein. 16 Recently, AKIP1 has been shown to facilitate tumorigenesis and invasiveness. [9][10][11][12] For example, one study displays that AKIP1 promotes cell migration, invasion, and EMT through mediating transactivating Zinc Finger E-Box Binding Homeobox 1 (ZEB1) in non-small-cell lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Infectivity was determined similarly as described for Mason-Pfizer monkey virus [65][66][67][68][69][70][71]. Briefly, culture media from HEK 293 cells transfected with psPAX2, pWPXLd-GFP, and pHEF-VSV-G vectors in a 1:1:1 ratio in the presence of test compounds were collected 48 h post-transfection and filtered through a 0.45-µm filter.…”
Section: Single-round Infectivity Assaymentioning
confidence: 99%
“…The sample preparation and measurements were carried out as described elsewhere [68,70,71]. The VSV-G GFP-HIV infected cells were analyzed with a BD FACS Aria III flow cytometer (Becton Dickinson) with the excitation at 488 nm and the emission separated by a 530/30 band pass filter.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…A-kinase interacting protein 1 (AKIP1), originally named breast cancer-associated protein 3, facilitates the nuclear translocation of catalytic subunit of protein kinase A (7,8). Recently, it has been reported that AKIP1 is viewed as a tumor promoter (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%